Child Labor Bans, Employment, and School Attendance: Evidence from Changes in the Minimum Working Age - Mireille Kozhaya; Fernanda Martínez Flores (Institute of Labor Economics (IZA), 2022)
This paper investigates the effect of a unique child labor ban regulation on employment and school enrollment. The ban implemented in Mexico in 2015, increased the minimum working age from 14 to 15, introduced restrictions to employ underage individuals, and imposed penalties for the violation of the law. Our identification strategy relies on a DiD approach that exploits the date of birth as a natural cutoff to assign individuals into treatment and control groups. The ban led to a decrease in the probability to work by 1.2 percentage points and an increase in the probability of being enrolled in school by 2.2 percentage points for the treatment group. These results are driven by a reduction in employment in paid activities, and in the secondary and tertiary sectors. The effects are persistent several years after the ban.
Keywords: I38; J22; J23; J82; O12; 330; child labor; ban; minimum working age; schooling